Exploring The Effects of a Short-Term S.T.E.A.M. Carnival on Female Secondary School Students' Attitudes and Motivation toward STEM Learning - Md Rashid, Siti Nafisah; Aadenan, Amin; Fitriana, Sheila (Jurnal Pendidikan IPA Indonesia, 2026)
Experiential learning is increasingly recognized as a pedagogical approach that bridges theoretical knowledge and practical application in STEM education, contributing to Sustainable Development Goals 4 (Quality Education) and 5 (Gender Equality) by promoting inclusive participation in STEM learning. This study explores female secondary school students' attitudes, motivation, and engagement in STEM learning following participation in hands-on electrical circuit activities conducted during a S.T.E.A.M. Carnival in Malaysia. Grounded in Kolb's Experiential Learning Theory, a mixed-method design involving structured experiential activities and a post-intervention questionnaire was employed. The participants consisted of 15 female secondary school students from diverse academic backgrounds in Malaysia. Descriptive statistics were used to examine students' perceptions of their learning experiences, motivation, and understanding of STEM concepts. The findings suggest that students generally held positive attitudes toward STEM, with personal curiosity and perceived career opportunities identified as the primary motivational factors. A large proportion of students reported a better understanding of physics concepts (93.3%) and greater confidence in scientific problem-solving (86.7%) following participation in the activities. Students also expressed strong preferences for hands-on and collaborative learning approaches, indicating positive perceptions of experiential learning as a means of supporting engagement and self-efficacy. Overall, the findings suggest that short-term experiential STEM interventions are associated with positive self-reported attitudes, motivation, and engagement among participating female students, highlighting the potential of experiential learning to support efforts to reduce gender disparities in STEM engagement. However, the study is limited by its small, female-only sample and reliance on self-reported data, underscoring the need for further research with larger, more diverse populations.